Effect of intermittent fasting on fasting blood glucose, sirtuin 1, and total antioxidant capacity in rat models of diabetes mellitus - Safitri, Meidiyani; Harliansyah; Wuryanti, Sri (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Background: Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycaemia. DM therapy is mainly purposed to control blood glucose levels by adjusting diet and reducing body fat, which can be implemented with calorie restriction (CR) by intermittent fasting (IF), a diet that alternates periods between eating and fasting. Sirtuins, proteins activated by CR, can regulate glucose metabolism, regulate insulin secretion, and protect cells from oxidative stress, so IF is considered to be an opportunity for DM management.Objective: This study is to determine effects of IF on Fasting Blood Glucose (FBG) levels, sirtuin 1 (SIRT1) activity, and total antioxidants (TAOC) in rat models of Wistar with DM.Methods: This experimental study applied a post-test control group design involving 24 Wistar rats which were divided into 4 groups: K1 (rats with DM without IF), K2 (rats with DM treated with metformin 45 mg/kg BW, K3 (rats with DM treated with IF), and K4 (normal rats treated with IF). The diabetes condition were induced with intraperitoneal injection of streptozotocin (STZ). The rats received IF treatment, fasted for 16 hours and ate window open for 8 hours. This treatment was conducted for 14 days. The FBG levels were measured by using a glucometer, while SIRT1 activity and TAOC were measured by using the ELISA method.Results: The statistical analysis using the Kruskal Wallis test for the FBG levels indicated that there was a significant difference among the four groups (p = 0.000). The ANOVA test for SIRT1 activity revealed that there was a significant difference among the four groups (p = 0.001). The Kruskal Wallis test for TAOC pointed out that there was no significant difference among the four groups (p = 0.529).Conclusion: The IF method using a 16:8 regimen reduced the FBG levels and increased the sirtuin 1 activity, but it was not proven to increase the TAOC in the rat models of Wistar with DM.